Cerebral dominance - evaluation of the methods of its determination and its clinical uses - P, Rama Mohan Babu; KC, Swarnalatha (Journal of All India Institute of Speech and Hearing, 1972)
In this paper the concept of cerebral dominance for various functions with emphasis on speech, is examined in the light of the recent literature available to us. A few ways in which this knowledge of cerebral dominance can be used in the differential diagnosis of speech disorders due to cortical lesions have been discussed. And, finally, some of the methods which help in determining the "dominant hemisphere" are pointed out